Central and Eastern European economies : perspectives and challenges - Goncalves, Marcus., (Economics collection., 2016)
This book provides relevant and timing information addressing a significant aspect of the economic, political, and social transition in Central and Eastern Europe (CEE) over the last several decades, integrating historical data with the most recent political and economic reporting based on the author's analysis. Analysis include assessments, opinions, and experience (where appropriate) as scholars, researchers, consultants, and global citizens, from an introduction to the historical context for European integration, including the political structures and economic relationships forged in the post-World War II period, to the relationship between the European Union and the economies of states in CEE, examining the political, economic, and security considerations that complicated the federalist relationship in each state, and end with a brief discussion of the adoption of the euro. This book also discusses the economic impact of integration of CEE countries as they attempt to make their economic transition and to integrate with the European Union and other free-market economies. The authors look at the economic growth and challenges these countries face, as well as how the indebtedness of the advanced economies are impacting these economies and prompting them to launch economic countermeasure to protect their own economies.